2014
DOI: 10.3390/coatings4030553
|View full text |Cite
|
Sign up to set email alerts
|

Recent Photocatalytic Applications for Air Purification in Belgium

Abstract: Photocatalytic concrete constitutes a promising technique to reduce a number of air contaminants such as NO x and VOC's, especially at sites with a high level of pollution: highly trafficked canyon streets, road tunnels, the urban environment, etc. Ideally, the photocatalyst, titanium dioxide, is introduced in the top layer of the concrete pavement for best results. In addition, the combination of TiO 2 with cement-based products offers some synergistic advantages, as the reaction products can be adsorbed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(61 citation statements)
references
References 18 publications
1
59
0
1
Order By: Relevance
“…In particular, photocatalytic wall reactors have been successfully applied in the control of air pollutants (Boonen and Beeldens 2014). Some works, however, showed that halogenated aliphatic hydrocarbons present the lowest photocatalytic conversion efficiencies when compared to other VOC types (Hodgson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, photocatalytic wall reactors have been successfully applied in the control of air pollutants (Boonen and Beeldens 2014). Some works, however, showed that halogenated aliphatic hydrocarbons present the lowest photocatalytic conversion efficiencies when compared to other VOC types (Hodgson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Italy, Belgium, China, and the United States, photocatalytic titanium dioxide (TiO 2 ) is added to sidewalk blocks, precast external building material, and the walls of large buildings such as theaters and stadiums; TiO 2 exhibits anti-fouling, deodorization, and air purification properties. Commercial TiO 2 is used in the construction of such conventional structures [4,5,6,7,8,9,10]. The most common crystalline phases of TiO 2 are rutile, anatase and brookite.…”
Section: Introductionmentioning
confidence: 99%
“…. ) [34][35][36][37][38]. Regarding bacterial and fungal disinfection, research has mainly focused on the efficiency of photocatalytic TiO 2 particles used alone, powdered or immobilized in the form of thin film coatings by complex processes (usually involving calcination).…”
Section: Introductionmentioning
confidence: 99%